Pro-Apoptotic Kinase Levels in Cerebrospinal Fluid as Potential Future Biomarkers in Alzheimer’s Disease - Paquet, Claire; Dumurgier, Julien; Hugon, Jacques (Frontiers in Neurology, 2015)
AAlzheimer’s disease (AD) is characterized by the accumulation of Aβ peptides, hyperphosphorylated tau proteins and neuronal loss in the brain of affected patients. The causes of neurodegeneration in AD are not clear but apoptosis could be one of the cell death mechanisms. According to the amyloid hypothesis, abnormal aggregation of Aβ leads to altered kinase activities inducing tau phosphorylation and neuronal degeneration. Several studies have shown that pro-apoptotic kinases could be a link between Aβ and tau anomalies. Here, we present recent evidences from AD experimental models and human studies that 3 pro-apoptotic kinases (double stranded RNA kinase (PKR), Glycogen Synthase Kinase-3β (GSK-3β) and C-Jun terminal kinase (JNK) could be implicated in AD physiopathology. These kinases are detectable in human fluids and the analysis of their levels could be used as potential surrogate markers to evaluate cell death and clinical prognosis. In addition to current biomarkers (Aβ 1-42, tau and phosphorylated tau) these new evaluations could bring about valuable information on potential innovative therapeutic targets to alter the clinical evolution.